Gaia astrometry and exoplanetary science: DR2, (E)DR3, and beyond - Sozzetti, Alessandro (Comptes Rendus. Physique)
I review the recent impact of Gaia astrometry in the exoplanet field, both in terms of characterization of the orbits and masses of planetary systems and the properties of their host stars. I then discuss the newly published results in the third major data release (DR3), that begin to tackle exoplanetary science based on Gaia data alone. I conclude with a perspective look at the expectations for major contributions to our understanding of exoplanet demographics from future Gaia data releases.